Tai Chi Chuan Alters Brain Functional Network Plasticity and Promotes Cognitive Flexibility - Cui, Lei; Tao, Sha; Yin, Heng-chan; Shen, Qi-qi; Wang, Yuan; Zhu, Li-na; Li, Xiu-juan (Frontiers in Psychology, 2021)
Objective: This study used resting-state functional MRI (fMRI) to investigate the effects of 8-week Tai Chi Chuan and general aerobic exercise on the topological parameters of brain functional networks, explored the advantages of Tai Chi Chuan for improving functional network plasticity and cognitive flexibility, and examined how changes in topological attributes of brain functional networks relate to cognitive flexibility. Methods: Thirty-six college students were grouped into Tai Chi Chuan (Bafa Wubu of Tai Chi), general aerobic exercise (brisk walking), and control groups. All the subjects underwent fMRI and behavioral assessment before and after the exercise intervention. Results: We found that Tai Chi Chuan exercise significantly enhanced the clustering coefficient and local efficiency compared with general aerobic exercise. Regarding the nodal properties, Tai Chi Chuan significantly enhanced the nodal clustering coefficient of the bilateral olfactory cortex and left thalamus, significantly reduced the nodal clustering coefficient of the left inferior temporal gyrus, significantly improved nodal efficiency of the right precuneus and bilateral posterior cingulate gyrus, and significantly improved the nodal local efficiency of the left thalamus and right olfactory cortex. Furthermore, the behavioral performance results demonstrated that cognitive flexibility was enhanced by Tai Chi Chuan. The change in nodal clustering coefficient in the left thalamus induced by Tai Chi Chuan was a significant predictor of cognitive flexibility. Conclusion: These findings demonstrate Tai Chi Chuan was able to promote brain functional specialization. Brain functional specialization enhanced by Tai Chi Chuan exercise was a predictor of greater cognitive flexibility.